Análise de desempenho de um sistema dual de armazenamento em microrredes isoladas baseadas em energia de correntes de maré - GOMES, Thiago Luis Campos (2019)
A microgrid can be defined as an electrical distribution system containing distributed generation and loads and can be operated in connection with the main grid or standalone mode. Due to the technological advances and incentives to reduce pollutants, unconventional renewable sources have been gaining prominence in the world's electrical matrix, especially in isolated systems. However, due to the intermittent characteristics of these sources, storage systems play a very important role in instantaneous generation/load balancing. In isolated microgrids, lead-acid batteries still dominate the market, however, their useful life is directly affected by how they operate. In this context, major investments are made for the development of methods and technologies that are capable of preserving the useful life of these systems. Flashing from renewable sources is the reason for using batteries, while they are also the reason for the premature aging of these components. One way to mitigate this problem is through a dual battery energy storage system (DBESS), which reduces the overall investment. However, this reduction is associated with the characteristics of the renewable source, and in the case of systems with a tidal current source, these benefits have not yet been evaluated. The renewable source used in this study is based on ocean energies, specifically tidal currents, which is non-polluting, and has a promising future, mainly because it has significant potential to be explored. This work uses a Dual Battery Energy Storage System (DBESS) formed by two storage subsystems with different functions and under different charge/discharge conditions, according to the characteristics of the tidal current source. To estimate the battery useful life, the Schiffer model was used to evaluate the benefits of the applied strategy.